PLASMA CONCENTRATION OF CURCUMIN AND SELENIUM FOLLOWING ADMINISTRATION OF SLOW-RELEASE CURCUMIN-LOADED SELENIUM NANOPARTICLES - KABOUTARI, JAHANGIR; SABAGHI, FATEMEH; ALTEMEMY, DHIYA; ARAB, HOSEIN ALI; JAVDAI, MOOSE; KHOSRAVIYAN, PEGAH (International Journal of Applied Pharmaceutics, 2025)
Objective: Suitable plasma concentration at the site of action is a crucial therapeutic goal, so slow-release pharmaceutical dosage forms have been very effective. This study planned to investigate the plasma concentrations of curcumin (Cur) and selenium nanoparticles (SeNPs) following the administration of a slow-release system of SeNPs loaded with Cur (SeNPs@Cur). Methods: 75 adult male rats were randomly divided into five groups. The control group received no treatment. In other groups, a single dose of 5 ml of 10% ethanol (solvent group), 0.25 mg/kg SeNPs, 50 mg/kg Cur, and 0.25 mg/kg SeNPs loaded with 50 mg/kg Cur (SeNPs@Cur) were administered intraperitoneally. Blood samples were taken on days 1, 3, and 5, and blood concentrations of SeNPs and Cur were measured by inductively coupled plasma atomic emission spectroscopy (ICP-AES) and High-performance liquid chromatography (HPLC), respectively. Results: The concentration of Cur in the Cur group was less than five µg on day 1 and gradually decreased over 5 d to zero. The blood concentration of Cur was approximately 15 µg on day 1 in the SeNPs@Cur group, then decreased until the 3rd day, and finally remained at a constant level of 5 µg on the 5th d. Selenium concentration decreased in the SeNPs group, from 160 µg on day 1 to 100 µg on day 5. Selenium concentration in the SeNPs@Cur group was 180 µg on the first day, then decreased to 110 µg on the fifth day. SeNPs@Cur maintained a plasma curcumin level of 5 µg on day 5 compared to undetectable levels in the Cur group. Conclusion: This study showed that the intraperitoneal administration of SeNPs@Cur, compared to the administration of free Cur, initially causes a high serum concentration and a loading dose, which continues with the slow release, increasing and maintaining the Cur serum level in the long-term treatment period.